The Importance of Islamic Religious Education in Shaping National Character - Wahib, Ahmad; Nafi’ah, Ayu Zahroh (STAI MA'ARIF MAGETAN, INDONESIA, 2022)
Character is closely related to the morals and morals of a person. Character is the values of human behavior related to God Almighty, one self, fellow human beings, the environment and nationality tat are manifested in thoughts, attitudes, feelings, words and deeds based on religious norms, laws, manners, culture and customs. The development of the nation’s character must be formed from the values instilled in the nation’s generation. Education is one the most appropriate pathways in efforts to builds the character the nation. Character education will grow well if it starts from the embedding of the spirit of diversity in children, therefore PAI is one of the supports for character education. In Islamic religious education, children are not only taught to understand religion, more than that they are educated to live and practice the values of the religious teachings they have mastered in daily life, both as individuals and citizens of the community.